Researcher’s Personal Profile on Academic Social Network Sites: Connection, Visibility, and Impact of Academic Work - Shah, Jay (Journal of Institute of Medicine Nepal, 2021)
A researcher's personal profile helps communicate and increase the visibility for academic work. Online personal profiles greatly enhance sharing of information and interaction with the academic community. This interaction and visibility further benefit in career advancement, funding, citation score, and many more. Academic Social Network Sites provide facilities for the creation of a personal profile that links the research and publications which can be verified easily and helps generate author-level metrics, unlike the traditional biodata.